Deformation and degradation of superelastic NiTi under multiaxial loading. (1st April 2019) - Hsu, Wei-Neng; Polatidis, Efthymios; Šmíd, Miroslav; Van Petegem, Steven; Casati, Nicola; Van Swygenhoven, Helena
Abstract: The degradation of the superelastic properties of a commercial NiTi alloy is studied during uniaxial, biaxial and load-path-change cycling performed in-situ with synchrotron X-ray diffraction. Careful examination of the diffraction pattern during uniaxial loading shows the R-phase as a transition between the austenite and the B19′ martensite. Degradation of the superelasticity is found to depend strongly on the loading and unloading path followed, and it is discussed in terms the B19′ martensitic variant selection, the accumulation of dislocations, and the residual R-Phase and B19' martensite. Cycling biaxially leads to faster degradation than uniaxially due to a larger accumulation of dislocations. If the deformation cycle contains a load path change, dislocation accumulation increases further and more martensite is retained. Graphical abstract: Image 1